2013
DOI: 10.1111/bph.12221
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H3 receptors, the complex interaction with dopamine and its implications for addiction

Abstract: Histamine H3 receptors are best known as presynaptic receptors inhibiting the release of histamine, as well as other neurotransmitters including acetylcholine and dopamine. However, in the dorsal and ventral striatum, the vast majority of H3 receptors are actually located postsynaptically on medium sized spiny output neurons. These cells also contain large numbers of dopamine (D1 and D2) receptors and it has been shown that H3 receptors form heterodimers with both D1 and D2 receptors. Thus, the anatomical loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 117 publications
(147 reference statements)
1
30
0
Order By: Relevance
“…Specifically, H3 receptors are found in high concentrations throughout the cortex, hippocampus and striatum [54], the latter of which has been strongly associated with TS pathophysiology. Moreover, H3 receptors in the striatum have been shown to have significant roles in modulating dopaminergic neurotransmission [59,60], thus further supporting their possible role in TS [61]. Specifically, histamine neurotransmission appears to reduce the concentration of dopamine in the striatum by acting at H3 heteroreceptors on dopaminergic afferents.…”
Section: Dopaminergic and Histaminergic Pathways In Tourette Syndromementioning
confidence: 91%
“…Specifically, H3 receptors are found in high concentrations throughout the cortex, hippocampus and striatum [54], the latter of which has been strongly associated with TS pathophysiology. Moreover, H3 receptors in the striatum have been shown to have significant roles in modulating dopaminergic neurotransmission [59,60], thus further supporting their possible role in TS [61]. Specifically, histamine neurotransmission appears to reduce the concentration of dopamine in the striatum by acting at H3 heteroreceptors on dopaminergic afferents.…”
Section: Dopaminergic and Histaminergic Pathways In Tourette Syndromementioning
confidence: 91%
“…H3R is coupled to G␣ i and thereby can reduce cAMP-mediated signaling, at least in some cells (7,30,31). This could oppose the effects of D1R activation on the cAMP/PKA/DARPP-32 signaling pathway.…”
Section: H3r Agonist Treatment Does Not Regulate the Camp/pkamentioning
confidence: 99%
“…A large proportion of H3Rs are located presynaptically on both histaminergic and non-histaminergic neurons. Without exception, stimulation of these presynaptic H3Rs inhibits the release of a neurotransmitter, including histamine, dopamine, acetylcholine, and glutamate [71]. A recent study has shown that the H3R located on histaminergic terminals is most likely a short isoform [H 3(431) ].…”
Section: Glossarymentioning
confidence: 99%
“…Several studies have now shown that large regional differences exist in the influence of H3R on neurotransmitter release. For instance, whereas in the prefrontal cortex H3R antagonists/inverse agonists enhance dopamine and histamine release, they have no such effect in the dorsal striatum (for an overview see [71]). …”
Section: Glossarymentioning
confidence: 99%
See 1 more Smart Citation